Relief Ramayana dan Cerita Kṛṣṇa di Candi Lara Jonggrang dan Pergantian Kekuasaan Mataram Kuna Abad Ke 9 Masehi - Andri Restiyadi (Berkala Arkeologi, 2020)
Lara Jonggrang is one of the temples in Java that attracts several researchers from various disciplines. The abundance of discussion about this temple does not necessarily close the possibility of new discussion or merely reinterpreting old problems through new approaches. One of the aims of this study is to reopen the old discourse about Lara Jonggrang Temple which is considered to have reached the final stage through research questions, What is the relation between the reliefs of the Rāmāyana story and the Kṛṣṇa story in Lara Jonggrang Temple and the transfer of power in the Ancient Mataram in 9th Century AD? Through a descriptive-analytical method, this study found several things that have been considered final have still kept a few surprises from new interpretations. Through this article, it is shown that Rakai Pikatan and Rakai Kayuwangi play a role as a milestone for the construction, inauguration, and carving of story reliefs in Lara Jonggrang Temple. In addition, the existence of the two reliefs is also related to the process of transfer of power in the Ancient Mataram in 9th Century AD.